EFFECT OF CALCIUM ON THE GROWTH AND ION UPTAKE IN NaCl-STRESSED PLANTS - Didy Sopandie; Toshio Kawasaki; Masumi Moritsugu (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1995)
Peanut and kidney bean gave similar response to salt stress showing a more severe growth reduction, as compared to spinach, leaf beet, barley cultivars and wild barley. Calcium showed the protective effect on salt injury in all plants, the effect of which was more pronounced in spinach, leaf beet and both types of barley plant than that in bean and peanut. High concentration of NaCl decreased the content of K, Ca, and Mg in both shoot and root of all plants. Elevated Ca in the nutrient solution, however. Considerably alleviated the inhibition of K uptake due to NaCl. The result suggested that the maintenance of K / Na selectivity by Ca in plant might result in the enhancement of salt tolerance.